2021
DOI: 10.1182/blood.2021011075
|View full text |Cite
|
Sign up to set email alerts
|

The clinical and functional effects of TERT variants in myelodysplastic syndrome

Abstract: Germline pathogenic TERT variants are associated with short telomeres and an increased risk of developing myelodysplastic syndrome (MDS) among patients with a telomere biology disorder. We identified TERT rare variants in 41 of 1514 MDS patients (2.7%) without a clinical diagnosis of a telomere biology disorder who underwent allogeneic transplantation. Patients with a TERT rare variant had shorter telomere length (p<0.001) and younger age at MDS diagnosis (52 vs. 59 years, p=0.03) than patients without … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 70 publications
3
16
0
Order By: Relevance
“…We also identified three lead variants at the TERT locus for which CH risk alleles were associated with longer LTL, a finding corroborated by our MR results linking increased LTL to CH. Interestingly, a recent study found deleterious rare germline TERT variants associated with shorter telomeres in patients with myelodysplastic syndromes 87 . However, compared with conventional myelodysplastic syndromes, these cases displayed a paucity of somatic mutations in DNMT3A (2 of 41) and TET2 (3 of 41 cases), suggesting that evolutionary paths may differ between cases with long versus short telomeres.…”
Section: Discussionmentioning
confidence: 99%
“…We also identified three lead variants at the TERT locus for which CH risk alleles were associated with longer LTL, a finding corroborated by our MR results linking increased LTL to CH. Interestingly, a recent study found deleterious rare germline TERT variants associated with shorter telomeres in patients with myelodysplastic syndromes 87 . However, compared with conventional myelodysplastic syndromes, these cases displayed a paucity of somatic mutations in DNMT3A (2 of 41) and TET2 (3 of 41 cases), suggesting that evolutionary paths may differ between cases with long versus short telomeres.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the absence of a family history of telomere-mediated disease does not preclude the presence of a germline mutation. TERT mutations may also manifest in children as aplastic anemia and in adults with myelodysplastic syndrome, where they also explain 3–5% of cases ( 54 , 66 , 67 ).…”
Section: The Genetic Basis Of Telomere-mediated Lung Diseasementioning
confidence: 99%
“…In telomere biology disorders (TBD), MDS and myeloid leukemia were the most commonly diagnosed cancers, with a median age at diagnosis of 53 years (range of 12–71 years old) ( 11 ). TERT mutations were identified in 2.7% of adult patients with MDS ( 12 ). DDX41 mutations associated with MDS and AML are characterized by presentation in older adulthood, often without any family history ( 13 , 14 ).…”
Section: Predisposition To Mds and Other Hematologic Malignancies Is ...mentioning
confidence: 99%